2021
DOI: 10.1017/s0031182021000196
|View full text |Cite
|
Sign up to set email alerts
|

Infection withTrypanosoma lewisiorTrypanosoma musculimay promote the spread ofToxoplasma gondii

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…If this was to be true co-infection rates observed in natural small mammal populations would be very reduced. At the same time, Gao and colleagues, [31] found that laboratory Norway rats infected with T. lewisi were more susceptible to T. gondii infections.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…If this was to be true co-infection rates observed in natural small mammal populations would be very reduced. At the same time, Gao and colleagues, [31] found that laboratory Norway rats infected with T. lewisi were more susceptible to T. gondii infections.…”
Section: Discussionmentioning
confidence: 92%
“…If this was to be true co-infection rates observed in natural small mammal populations would be very reduced. At the same time, Gao and colleagues, [31] found that laboratory Norway rats infected with T. lewisi were more susceptible to T. gondii infections. Although this does not necessarily remain true for wild rodents, a fortiori for wild black rats, a T. lewisi -induced increased susceptibility to T. gondii would be expected to an increase in the proportions of co-infected animals [27–31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, natural coinfection by T. gondii and T. cruzi has already been reported in a female red-necked wallaby that had sudden death but did not present clinical signs but microscopic and molecular analysis confirmed T. gondii cysts and T. cruzi genotype I ( 27 ). In an experimental study, T. lewisi infection increased the susceptibility of Sprague–Dawley rats to T. gondii infection, and this phenomenon was associated with the reduction in the production of nitric oxide (NO) and inducible nitric oxide synthase (iNOS) in peritoneal macrophages ( 28 ), important molecules for the control of T. gondii infection ( 29 ), favoring its dissemination in the host, showing that in situations of coinfection, the presence of a pathogen can favor infection by another pathogen.…”
Section: Introductionmentioning
confidence: 99%